2016
DOI: 10.1080/09540261.2016.1191449
|View full text |Cite
|
Sign up to set email alerts
|

Self-transcending meditation is good for mental health: why this should be the case

Abstract: A simple theory of health has recently been proposed: while poor quality regulation corresponds to poor quality health so that improving regulation should improve health, optimal regulation optimizes function and optimizes health. Examining the term 'optimal regulation' in biological systems leads to a straightforward definition in terms of 'criticality' in complexity biology, a concept that seems to apply universally throughout biology. Criticality maximizes information processing and sensitivity of response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One study claimed that 30 min of meditation is enough for a beginner to reduce stress (Sharma, 2015). Peacefulness and the reduction of stress are important for improving brain functions, especially cortical brain functions (Hankey and Shetkar, 2016). Theta activity has been utilized to investigate the meditative state by both general theta and frontal midline theta rhythms (Takahashi et al, 2005; Lagopoulos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One study claimed that 30 min of meditation is enough for a beginner to reduce stress (Sharma, 2015). Peacefulness and the reduction of stress are important for improving brain functions, especially cortical brain functions (Hankey and Shetkar, 2016). Theta activity has been utilized to investigate the meditative state by both general theta and frontal midline theta rhythms (Takahashi et al, 2005; Lagopoulos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The future journey of this research will depend on what can be shown to be scientific and what can be proven. It should build on our understanding of the biophysics of meditation,[43] its relationship to self-organized criticality,[4445] subjective accounts of meditation from the first person perspective,[46] building the Panchakosha model,[47] and similar reasoning to show how meditation benefits mental health[4544] enhancement of higher brain faculties such as an emotional intelligence,[48] redefining social consciousness through human excellence,[49] and cognition of pure consciousness, by the application of its structure in the Vedic sciences. [50]…”
Section: Discussionmentioning
confidence: 99%
“…Many of the components, tools, and methods employed in the workshop are supported by previous studies demonstrating their ability to positively affect self-esteem. These include cognitive behavioral therapy (Thurston et al, 2017 ), meditation (Dahl et al, 2015 ; Fabiani et al, 2016 ; Hankey and Shetkar, 2016 ; Xiao et al, 2017 ), creative visualization (Fiske, 2017 ), introspective reflection and writing (Lauer and Goldfield, 1970 ; Chandler, 1990 ), self-care mindfulness (Adimando, 2017 ), ceremonial ritual (Wozniak and Allen, 2012 ), and self-compassion and mindfulness (Galla, 2016 ).…”
Section: Discussionmentioning
confidence: 99%